Analisis Pasar Tenaga Kerja Dalam Perspektif Ekonomi Islam - Wahyu Syarvina; Fitriani Saragih; Isnaini Harahap (JRAK (Jurnal Riset Akuntansi dan Bisnis), 2022)
Employment problems are very important and complex problems. In Islamic economics, the problem of labor welfare always gets attention when looking at the labor market, so the scope of the labor market from a macroeconomic point of view not only tends to create favorable economic conditions, but also policies that determine the ideal wage that can lead to the power to create people's welfare as a fundamental tool of a country. The purpose of this study is to see how the labor market in an Islamic perspective. The type of research method in this research is qualitative research, namely library research that is sourced from books and other documents as the main object. Determination of wages in Islam depends on the needs of workers based on justice and honesty and protects the interests of employers and workers. The impact of the implementation of a labor market that is Islamic in nature can potentially create economic equity in society and develop the economy and welfare, as is expected to achieve falah in sharia economy